2015
DOI: 10.1111/ijmr.12052
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Entrepreneurship: A Review and Research Agenda

Abstract: A systematic review of the entrepreneurship literature on fear published up to 2014 highlights several key characteristics. First, the predominant focus in research examining the emotion of fear in entrepreneurship is on the specific concept of fear of failure. However, this literature shows a lack of precision in the conceptualization and operationalization of this construct. The impact of the experience of fear on individual cognition and behaviour can be beneficial as well as detrimental. Despite this duali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
217
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(266 citation statements)
references
References 132 publications
6
217
0
6
Order By: Relevance
“…We do not argue that fear of failure reflects a general risk aversion. Nor do we claim that fear of failure prevents people to start a firm by hook or by crook (for a fruitful critical discussion, see Hayton et al, 2013 andHayton, 2015). We rather regard the formation of fear of failure as a contextspecific process that is affected by social interactions with entrepreneurs in the local environment and can negatively affect entrepreneurial propensity.…”
Section: Introductionmentioning
confidence: 92%
“…We do not argue that fear of failure reflects a general risk aversion. Nor do we claim that fear of failure prevents people to start a firm by hook or by crook (for a fruitful critical discussion, see Hayton et al, 2013 andHayton, 2015). We rather regard the formation of fear of failure as a contextspecific process that is affected by social interactions with entrepreneurs in the local environment and can negatively affect entrepreneurial propensity.…”
Section: Introductionmentioning
confidence: 92%
“…Since, there is a general tendency to question entrepreneurial outcomes as either success or failure, FoF is often included in entrepreneurship research. Thus, entrepreneurs are motivated towards doing their best and endowed with an idea of avoiding failure in business life through effective opportunity identification, selection or development, maximum performance on entrepreneurial tasks and action (Cacciotti, and Hayton, 2015). Moreover, such a fear is regarded as a psychological barrier for entrepreneurial intent and action.…”
Section: The Role Of Fof In Shaping Occupational Choicesmentioning
confidence: 99%
“…Therefore, FoF could produce both approach and avoidance behaviours. Despite significant efforts towards a new understanding which instills an idea of every failure is a learning opportunity, negative connotation is prevailing in the field (Cacciotti, and Hayton, 2015). Career intention literature has been shaped particularly around entrepreneurial intention and an intention of being a paid employee.…”
Section: The Role Of Fof In Shaping Occupational Choicesmentioning
confidence: 99%
“…While some research has indicated that an anti-failure bias is manifest in a fear of failure and that a fear of failure usually leads to inaction (Alon and Lerner 2008; Wagner and Stenberg; for a review, see Cacciotti and Hayton 2015), some individuals appear to be able to overcome their fears and go after potential opportunities. 1 These actions are vital in creating wealth for individuals, organizations, and national economies Sarasvathy 2001).…”
Section: Fear Motivating Entrepreneurial (In)actionmentioning
confidence: 99%